The envoy [large type] : the epic rescue of the last Jews of Europe in the desperate closing months of World War II - Kershaw, Alex (Thorndike Press, 2010)
December 1944. In the blood-strewn suburbs of Budapest crazed Hungarian fascists join die-hard Nazis to slaughter Jews day and night. In less than six months, SS Colonel Adolf Eichmann sent over half a million Hungarians to Auschwitz. All that stands between him and Europe's last Jewish ghetto is an unarmed Swedish diplomatic envoy named Raoul Wallenberg. This is the stirring tale of how one man saved more than 100,000 Jews from extermination.